Morphometric and immunohistochemical features of TTF-1 positive lung tumors: improvement of approaches to the diagnosis of unknown primary sites metastases - Poslavska, Oleksandra; Shponka, Igor (ScienceRise: Medical Science, 2020)
Verification of lung tumors in the practical activity of a pathomorphologist reached a completely different level due to the use of additional highly sensitive diagnostic methods (immunohistochemical (IHC) and cytogenetic studies). Thyroid transcription factor 1 (TTF-1) plays a key role in lung morphogenesis and is expressed in about 90 % of pulmonary small cell carcinomas. The positivity of TTF-1 in pulmonary and extrapulmonary neuroendocrine tumors is actively debated in the literature, therefore, the results of IHС on TTF-1 in metastases from an unknown source should be interpreted carefully and constantly improve differential diagnostic algorithms, expanding IHC panels with organ-specific markers, and focus on additional morphometric indicators research of nuclei of tumor cells. The aim of the work is to investigate the complex of morphological, morphometric, and IHC characteristics of TTF-1 positive lung tumors to improve the diagnostic algorithms for metastases from an unknown primary source. Materials and methods. A retrospective analysis of histological, morphometric and IHC characteristics of the biopsy material TTF-1 of positive lung carcinomas from 36 patients (10 women and 26 men) aged 29 to 81 years (mean 58.03±10.83 years) for the period 2015–2018, taken from the archive of the morphological department of the medical-diagnostic center of LLC “Pharmacies of the Medical Academy” (Ukraine, Dnipro). Results. In the diagnosis of carcinomas of unknown primary localization with suspected lung origin, it is necessary to take into account morphological, morphometric and IHC features together, which is associated with the similarity of metastases of squamous cell carcinomas of the head and neck, mucinous adenocarcinomas of the gastrointestinal tract and neuroendocrine carcinomas from Merkel cells corresponding to the histological forms lung tumors, as well as insufficient sensitivity of the marker TTF-1. Conclusions. Use of the minimum primary (Cytokeratin, Pan AE1 / AE3 (+) / Vimentin (- / +) / CD45 (-) / S100 (- / +)) and secondary (Ck 7 +, Ck 20 -, TTF-1 + ) IHC panels will prove that the phenotype of carcinoma of unknown primary site corresponds to the form of disseminated lung carcinoma, and additional markers Сk HMW, p63, Chromogranin A, Synaptofisin and / or CD56 together with morphometric indices of the nuclei will determine the histological form of lung carcinoma with justification for the use of appropriate therapy